Interactome based biomarker discovery for irritable bowel syndrome—A systems biology approach. (October 2018) - Kalva, Sukesh; Bindusree, Ganigara; Alexander, V.; Madasamy, Parani
Graphical abstract: Highlights: A systems biological approach was used to identify potential biomarkers for IBS. Transcriptome analysis revealed differentially expressed genes that can regulate IBS. Gene prioritization studies identified 10 genes as candidate biomarkers for IBS. Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal (GI) disorder around world with no standard therapy. Till date, the pathophysiology of IBS is not clearly understood due to complexity of the disease. Current study reveals the underlying mechanism of IBS using systems biological approach. The complexity of IBS was explained by constructing protein-protein interaction (PPI) network from the text mined genes/proteins. PPI network displayed 68822 interactions from 3595 proteins. IBS interactome was mapped with colon tissue interactome which resulted in a sub-network containing 153 genes. Further, MCL algorithm was applied to sub-network to identify six major clusters. These cluster genes are involved in several pathways such as MAPK, PI3K/Akt, and NF-kappa B. The obtained clustered genes were prioritized using differentially expressed transcriptome data of 45 IBS and 45 normal volunteers. Among the differentially expressed genes, FUS, UNC5CL and BCLAF1 were found in the clusters, suggesting that the identified clusters could play a potential role in the regulation of IBS. Further pathway analysis of cluster genes revealed their molecular association with IBS. Gene prioritization studies identified top 10 genes that can be used as candidate biomarkers for early diagnosis of IBS. Out of top ten genes, PRPF31 was expressed in all biofluids (serum, saliva and urine).